Type 2 diabetes management in people aged over seventy-five years: targets and treatment strategies. (January 2021) - Koufakis, Theocharis; Grammatiki, Maria; Kotsa, Kalliopi
Highlights: Older adults with diabetes have special needs and features. Glycemic targets for older patients with diabetes should be individualized. Data on the efficacy and safety of antidiabetic agents in older patients are limited. Glucagon-like peptide-1 receptor agonists might improve glucose-independent outcomes in older people with diabetes. Abstract: Older people (those aged 65 years or more) with diabetes comprise a heterogenous group of patients with special needs and features; this is particularly true for those aged 75 years or more. It is important that individualized glycemic targets be adopted in this population, after considering life expectancy, presence of diabetic complications and other comorbidities. In general, less rigorous targets and avoidance of overtreatment seems to be a reasonable strategy in daily clinical settings. There is a paucity of data regarding the efficacy and safety of various hypoglycemic agents, especially for those aged over 75. The evidence suggests that sulfonylureas and insulin regimens should be used with caution due to a high risk of hypoglycemia. Dipeptidyl peptidase-4 inhibitors are a good choice for the management of diabetes in older age groups, although a warning against the use of specific agents in people with heart failure is valid. There are insufficient data to decide whether the cardiorenal protective properties of sodium-glucose co-transporter 2 inhibitors outweigh the risks associated with these drugs. The use of glucagon-like peptide-1 receptor agonists by older patients is supported not only by their good safety and efficacy profiles, but also by their potential to improve glucose-independent outcomes, through their pleiotropic actions. The aim of this narrative review is to summarize the evidence on glycemic targets and optimal therapeutic approaches for older patients with type 2 diabetes and discuss the risk-benefit balance of various therapeutic approaches in this group.